A citizen’s guide to waste incineration - Todorović, Mirjana (Napredak, 2025)
Waste incineration is a controversial topic, even in technologically advanced and highly industrialized countries. Due to the complexity of this issue, it is necessary to approach the analysis from a broader perspective that encompasses all relevant aspects of the incineration process. This paper examines not only the technological dimensions but also the institutional conditions that support the implementation of the waste management hierarchy, as well as the principles of proximity and self-sufficiency. Special attention is given to the energy recovery of waste through various incineration and co-incineration technologies, with a focus on mechanisms that enable the control and reduction of harmful emissions.
Keywords: waste incineration; incineration; landfills; pollution; waste-to-energy